STRATEGI PEMBENTUKAN KARAKTER RELIGIUS ANAK ASUH PANTI PELAYANAN SOSIAL ANAK (PPSA) KASIH MESRA - Amania, Fatimah Nila (Rabbani: Jurnal Pendidikan Agama Islam, 2024)
This research was carried out because it was motivated by cases of many character abuses committed by children, especially children who had disadvantaged family backgrounds. Whether it is the absence of parents, or economic problems that make children less concerned about character formation, especially religious character. The aim of this research is to describe the formation of the religious character of foster children at the Kasih Mesra Demak Children's Social Services Home (PPSA). In this research, the type of research used is descriptive qualitative field research. This research uses data collection methods in the form of interviews, observation, documentation and questionnaires. Based on the research that has been carried out, the researchers obtained the results that the religious character of foster children is formed through providing understanding through guidance, the example of orphanage caregivers, and through scheduled habituation activities. Activities that focus on methods of providing understanding can be seen in the activities of providing guidance, namely: biological, psychological, social and religious guidance. Activities that focus on the habituation method applied at PPSA Kasih Mesra Demak are: congregational prayers, reciting the Koran, gatherings and praying together, as well as all activities that have been carried out. The exemplary method used to shape the religious character of foster children is, imitating the daily behavior of caregivers and PPSA employees, for example, discipline during prayer times and teaching children the Koran, honesty in providing children's rights, fairness in caring for children, and tawadhu' in get along..